Pengembangan Modul Sistematika Tumbuhan Tinggi Berbasis Guided Discovery untuk Mengembangkan Kemampuan Berpikir Kritis Mahasiswa Pendidikan Biologi - Anwari Adi Nugroho; Singgih Subiyantoro (BIO-PEDAGOGI, 2017)
This study aimed to know the characteristic of high plants systematics module based guided discovery in developing the ability to critical thinking for biology education students and to know the validity and practicality of it. This research used modified Borg & Gall's method that was research and information collecting, planning, develop preliminary from of product, preliminary field testing, main product revision, main field testing, operational product revision. The product was high plants systematics module based guided discovery that a valid and practical. Characteristic of this high plants systematics module based guided discovery was contains activities with stimulation, problem statement, data collection, data processing, verification, and generalization. The result of preliminary field testing include learning module expert validation, module expert validation and learning materials expert validation indicated that the module was feasible and did not need any revision. The results of main field testing included practitioner and student test shows that the module is feasible (practical).